2022
DOI: 10.1042/ebc20210064
|View full text |Cite
|
Sign up to set email alerts
|

HECT ubiquitin ligases as accessory proteins of the plant proteasome

Abstract: The proteasome plays vital roles in eukaryotic cells by orchestrating the regulated degradation of large repertoires of substrates involved in numerous biological processes. Proteasome dysfunction is associated with a wide variety of human pathologies and in plants severely affects growth, development and responses to stress. The activity of E3 ubiquitin ligases marks proteins fated for degradation with chains of the post-translational modifier, ubiquitin. Proteasomal processing of ubiquitinated substrates inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
2
8
0
Order By: Relevance
“…These observations are also consistent with previous reports of E3 ligases associated with the proteasome, including HECT E3 ligases [72] and yeast UBR1 [87]. In yeast, the HECT E3 ligase UFD4 binds UBR1 and increases processivity of polyubiquitination [88]; similarly in plants, substrates from diverse E3 ligases are relayed to UPLs which prevent substrate stalling at the proteasome [72]. Given that UBR4 interacts with a diverse array of protein partners including E2 ubiquitin conjugating enzymes and E3 ligases to degrade both Ndegron pathway substrates and other protein targets [43,45,89], it is plausible that BIG serves as a versatile recognition component of the Arg/N-degron pathways and possibly other proteostatic mechanisms, interacting with one or more E3 ligases to mediate proteasomal degradation of a broad range of substrates (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These observations are also consistent with previous reports of E3 ligases associated with the proteasome, including HECT E3 ligases [72] and yeast UBR1 [87]. In yeast, the HECT E3 ligase UFD4 binds UBR1 and increases processivity of polyubiquitination [88]; similarly in plants, substrates from diverse E3 ligases are relayed to UPLs which prevent substrate stalling at the proteasome [72]. Given that UBR4 interacts with a diverse array of protein partners including E2 ubiquitin conjugating enzymes and E3 ligases to degrade both Ndegron pathway substrates and other protein targets [43,45,89], it is plausible that BIG serves as a versatile recognition component of the Arg/N-degron pathways and possibly other proteostatic mechanisms, interacting with one or more E3 ligases to mediate proteasomal degradation of a broad range of substrates (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with this, BIG copurified with proteasome subunits and UPL1/3 in transiently transfected Nicotiana benthamiana [60] and UBR4 is present at the proteasome at significant, but sub-stoichiometric amounts in mammals [85,86]. These observations are also consistent with previous reports of E3 ligases associated with the proteasome, including HECT E3 ligases [72] and yeast UBR1 [87]. In yeast, the HECT E3 ligase UFD4 binds UBR1 and increases processivity of polyubiquitination [88]; similarly in plants, substrates from diverse E3 ligases are relayed to UPLs which prevent substrate stalling at the proteasome [72].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As described in previous review, the HECT E3 N-terminus not only simply serves as an adapter for direct binding but it also provides various ways to regulate HECT E3s’ substrate recruitment and catalytic activity ( Lan & Miao, 2019 ; Wang & Spoel, 2022 ). In this study, we showed that UPL3 seemed to interact with histone variants, histone modifiers (BRM), PPC2, HXK1, several U-box proteins (UBC35), and DUBs (UBP12) in the nucleus ( Figs 6 and S8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of UPS substrates requires the concerted action of E1, E2, and E3 enzymes, which execute the functions of ubiquitin (Ub) activation, Ub‐conjugation, and Ub‐ligation, respectively (Vierstra, 2009). One important class of Ub‐ligating enzymes is the HECT E3s, which all contain a conserved domain with homology to the C‐terminus of human E6‐Associated Protein (E6‐AP) that functions in the degradation of p53 protein (Marín, 2013; Wang & Spoel, 2022). The Arabidopsis genome contains seven HECT‐containing proteins termed ubiquitin‐protein ligase 1(UPL1)‐UPL7, and UPL3 has a specific role in trichome development (Downes et al., 2003).…”
Section: Introductionmentioning
confidence: 99%